Experimental Study of the Air Resistance of Microchannel Heat Exchanger with Flat Tube and Louver Fin - Zhang Jianfei; Qin Yan; Kong Xiangguo (Zhileng xuebao)
An experimental study on the air-side resistance characteristics for micro channel heat exchanger has been performed. A series of tests were conducted at a constant surrounding temperature of 20℃ for the air velocity of 1-4m/s, Reynolds numbers of 100–500 and surface dimension of 600mm×550mm. The data were compared with different general correlations. The results show that there is a big difference between different correlations. Davenport’s predication is the best one, but the experimental data was only 55%-66% of predicted result. The data were compared with the plain fin and round tube heat exchanger with same surface dimension and capacity. The results show that they are near. The flat tube and lesser depth are two effective ways to reduce the air resistance.